2007
DOI: 10.1213/01.ane.0000278736.81133.26
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Effect of Sildenafil on Pulmonary Artery Smooth Muscle Cells Is Mediated via Upregulation of Mitogen-Activated Protein Kinase Phosphatase-1 and Degradation of Extracellular Signal-Regulated Kinase 1/2 Phosphorylation

Abstract: This study indicates that sildenafil upregulates MKP-1 expression and promotes degradation of phosphorylation of ERK1/2, which suppresses the proliferation of pulmonary artery smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Chronic sildenafil treatment attenuated medial hypertrophy in large arteries and completely prevented vascular remodeling in medium-sized and small arteries. This finding is in line with the welldocumented antiproliferative effect of sildenafil, 22,25 which has been attributed to mechanisms including stimulation of the cGMP-dependent protein kinase and regulator of G protein signaling 2 pathway, 25 to upregulation of mitogen-activated protein kinase phosphatase-1 and inhibition of extra- cellular signal-regulated kinase 1/2 phosphorylation, 26 as well as to inhibition of reactive oxygen species generation and RhoA/Rho kinase activation. 27 Although the prevention of lung vascular remodeling by sildenafil was paralleled by a complete normalization of PVR, CHF-induced pulmonary hypertension was only partially reversed, and PAP remained elevated by Ϸ2 mm Hg (without reaching PϽ0.05), reflecting the persistent increase in LAP as a consequence of the sustained banding.…”
Section: Lung Vascular Remodelingsupporting
confidence: 82%
“…Chronic sildenafil treatment attenuated medial hypertrophy in large arteries and completely prevented vascular remodeling in medium-sized and small arteries. This finding is in line with the welldocumented antiproliferative effect of sildenafil, 22,25 which has been attributed to mechanisms including stimulation of the cGMP-dependent protein kinase and regulator of G protein signaling 2 pathway, 25 to upregulation of mitogen-activated protein kinase phosphatase-1 and inhibition of extra- cellular signal-regulated kinase 1/2 phosphorylation, 26 as well as to inhibition of reactive oxygen species generation and RhoA/Rho kinase activation. 27 Although the prevention of lung vascular remodeling by sildenafil was paralleled by a complete normalization of PVR, CHF-induced pulmonary hypertension was only partially reversed, and PAP remained elevated by Ϸ2 mm Hg (without reaching PϽ0.05), reflecting the persistent increase in LAP as a consequence of the sustained banding.…”
Section: Lung Vascular Remodelingsupporting
confidence: 82%
“…Sildenafil, a selective PDE5 inhibitor, has been found to suppress PASMC proliferation by several mechanisms (Li et al, 2007;Li et al, 2009;Wang et al, 2009;Wang et al, 2008). In this study, we demonstrated that inhibition of PDE5 by sildenafil also suppressed serotonin-induced activation of the calcineurin/NFATc2 signaling pathway and consequent cyclin A upregulation, CDK2 activation and DNA synthesis, suggesting that the calcineurin/NFAT cascade is another major target of sildenafil in the pulmonary system.…”
Section: Discussionsupporting
confidence: 52%
“…Pulmonary arterial hypertension, is a condition characterized by an increase in pulmonary vascular resistance, thrombosis formation, pulmonary vascular remodeling [21][22][23][24][25], structural remodeling of the heart [26], right heart dysfunction and widespread loss of pulmonary microvasculature that carries blood from the heart to the lungs. Although in the past ten years, the treatment of PAH had an apparent progress, but the prognosis is still poor.…”
Section: Discussionmentioning
confidence: 99%